Valsts nodrošinātā juridiskā palīdzība Latvijā un pasaulē - Maksimovs, Roberts (Latvijas Universitāte, 2021)
Valsts nodrošināta juridiskā palīdzība ir viens no taisnīgas tiesa sastāvdaļām. Īpaši svarīga šāda palīdzība ir kriminālprocesā, jo nodrošina personu ar advokāta aizstāvību. Lai gan tiesiskais regulējums ir izstrādāts, tas ir jāpilnveido, ņemot vērā citu valstu tiesu praksi. Bakalaura darba mērķis ir izpētīt valsts nodrošinātās juridiskās palīdzības saņemšanas tiesisko regulējumu Latvijā un citās valstīs, konstatējot problēmjautājumus tiesiskajā regulējumā. Darba mērķa sasniegšanai tiek izvirzīti šādi uzdevumi: 1) analizēt valsts nodrošinātās juridiskās palīdzības saņemšanas vispārīgos nosacījumus; 2) pētīt valsts nodrošinātās juridiskās palīdzības saņemšanu atsevišķos procesos; 3) izpētīt valsts nodrošinātās juridiskās palīdzības saņemšanas tiesisko regulējumu citās valstīs.

State-provided legal aid is one of the components of a fair trial. Such assistance is particularly important in criminal proceedings, since it provides a person with a lawyer's defence. Although the legal framework has been developed, it needs to be further developed in the light of other countries' practices. The aim of the bachelor's work is to explore the legal framework for receiving legal assistance provided by the State in Latvia and other countries, identifying issues in the legal framework. In order to achieve the objective of work, the following objectives are identified: 1) to analyse the general conditions for the receipt of legal assistance provided by the State; 2) to study the receipt of legal assistance provided by the State in separate processes; 3) to examine the legal framework for the receipt of legal aid provided by the State in other countries.
State-provided legal aid in Latvia and in the world
Keywords: Juridiskā zinātne; valsts nodrošinātā juridiskā palīdzība; kriminālprocess; aizstāvība; pārstāvība